Prospective Application of the Erythrocyte Sedimentation Rate (ESR) as a Possible Inflammatory Marker in Feline Patients - Eleonora Gori; Anna Pasquini; Saverio Paltrinieri; George Lubas; Carlo Militello; Daniela Diamanti; Carlo Carletti; Marianna Pantoli; Veronica Marchetti (Veterinary Medicine International)
The application of the erythrocyte sedimentation rate (ESR) in feline medicine is currently unavailable, while in canine medicine it has been rediscovered due to the introduction of an automated ESR device. Our aims were to (1) define the reference interval (RI) of the ESR in healthy cats, (2) evaluate the ESR values between healthy and ill cats, (3) evaluate relationships between the ESR and some inflammatory markers, and (4) assess ESR changes in different durations of illness (acute, chronic, or acute-on-chronic). A prospective multicentric cohort study on 200 client-owned cats: 57 healthy cats and 143 ill cats for the other aims. Healthy cats were blood donors, or young cats underwent desexing procedures. Ill cats with full clinical medical records, hematobiochemical profiles, and diagnostic procedures to reach a final diagnosis were included. The ESR was performed with MINI-PET using the same K3-EDTA tubes used for CBC, with no additional sample required. The total leukocyte count (WBC), neutrophil-to-lymphocyte ratio (NLR), fibrinogen, serum amyloid A, and albumin/globulin ratio (A/G) were concurrently measured. Based on the clinical presentation and the final diagnosis, cats were classified as having the following: acute, chronic, and acute-on-chronic conditions. The RI of the ESR ranged between 1 and 23 mm/h. Ill cats showed a significantly higher ESR (median 29 mm/h; range 12–46 mm/h) than healthy cats (median 10 mm/h; range 1–12 mm/h; p<0.0001). The ESR was positively correlated only with fibrinogen (p<0.001; r = 0.43). Cats with acute-on-chronic diseases had the highest ESR (median 47 mm/h; range 35–56 mm/h) compared with acute (median 16 mm/h; range 14–42 mm/h; p=0.003) and chronic cats (median 14 mm/h; range 10–31 mm/h; p<0.0001). Although further studies are needed, the ESR could be a useful ancillary inflammatory marker in cats, specifically in cats with acute diseases, with or without an underlying chronic condition.